JavaScript for beginners get to grips with fundamental JavaScript concepts - Svekis, Laurence (Packt Publishing, 2018)
"JavaScript is easy to get started with; if you have ever wanted to learn JavaScript, then this is the course for you. You will be amazed at how much JavaScript can do and how easily you can make things happen using JavaScript. Please note that previous web experience is required for this course. A basic knowledge of HTML and CSS will be extremely helpful. The scope of this course involves introducing students to the basic core concepts of JavaScript. JavaScript is a scripting language used everywhere across the web. It is used to enhance HTML web pages and works within HTML files. JavaScript is also an interpreted language, so it doesn't need to be compiled: all you need is a browser to run the code. JavaScript enhances web pages with interactive and dynamic capabilities."--Resource description page
Title from resource description page (Safari, viewed November 5, 2018)
Keywords: JavaScript (Computer program language); Application software -- Development; Web site development; JavaScript (Langage de programmation); Logiciels d'application; Développement; Sites Web; Développement; Application software; Development; Instructional films; Films de formation